Management of Guidance and Counseling Service Based Cybercounseling in Madrasah in The New Normal Era - Hary Priatna Sanusi; Neng Gustini; Yaya Suryana; Ahmad Almafahir (STAI Hubbulwathan Duri, 2022)
The Covid-19 pandemic has brought many transformations and adjustments to our daily activities, including the learning process. Counseling guidance service is a supporting element in the learning process. Teenagers, especially students during the Covid-19 pandemic, face many psychological problems, which result in the need for assistance to help alleviate their problems. One of the forms of assistance is by providing guidance and counseling services. This study aims to understand and identify the management of guidance and counseling services based on cybercounseling in the new normal. The research applies a descriptive method with a qualitative approach, and the type of research is library research. The technique for collecting data is to study various reference sources or literature studies related to cybercounseling. The study results stated that the management process for guidance and counseling services based on cybercounseling was the same as the face-to-face counseling process, only that it was necessary to pay attention to the preparation of the equipment used. The advantage of this service is that it can be accessed anywhere and anytime based on mutual agreement. In comparison, the weakness is that students who have never attended counseling before have difficulties developing and predicting appropriate intervention techniques.